Geology of Bayat Area, Klaten and Volcanic Hazard of Mount Merapi, Central Java, Special Province of Yogyakarta, Indonesia - Maizathul Amiera Norzaimi (2019)
Geological research includes geological structure, geomorphology, lithology and petrography in Bayat Area, Klaten with coordinate 110⁰ 37’ 39.78” E - 110⁰ 39’ 46.9” E and latitudes 7⁰ 44’ 17.58” S - 7⁰ 46’ 24.78” S. The previous map of Bayat have a scale or 1:100,000 so the area of Bayat does not clearly cover and accurated. The area of the location is approximately 25 km². The study area for this research is 5 km × 5 km wide. The objective of this research are to update the current geological map of the area and to analyzed the volcanic hazard in Mount Merapi. As the previous eruption of Merapi was on 2010, and considered as one of the most tragic eruption, the hazard till can be seen till today and still remembered by most villagers nearby of the destruction. The method used in this study is by geological mapping and analysis of rock sample. Mount Merapi located at the Central Java of Indonesia and is one of the most active volcanoes in the world. Krasak River is one of the main river of the lahar flow and was chosen to study of lahar deposition. The lahar still can be observed there as the site now becomes the mining site. The impact from the eruption was very destructive and the impact can be observed on the nearest village which totally lost from the eruption now becomes a museum and shows the actual destruction from the previous eruption. The volcanic hazard in Mount Merapi is identified. Both geological map and hazard map can be used by the government of Yogyakarta in the future and the hazard map can prevent more lost of life.